Comparison of Biomechanical Failure Loads Between Tape-Type and Conventional Sutures in Internal Knotless Anchor–Based Constructs. Issue 3 (24th March 2022) - Chuang, Hao-Chun; Yen, Joe-Zhi; Hong, Chih-Kai; Hsu, Kai-Lan; Kuan, Fa-Chuan; Chen, Yueh; Chang, Hao-Ming; Su, Wei-Ren
Background: Despite the increasing prevalence of tape-type sutures, whether internal knotless anchors can consistently affix tape-type sutures has not been thoroughly investigated. Purpose: To evaluate whether substituting tape-type sutures for conventional sutures influences the suture-holding strength of internal knotless anchors. Study Design: Controlled laboratory study. Level of evidence, 5. Methods: A total of 3 internal knotless anchors were tested: a spiral core clamping anchor (Footprint Ultra PK), a winged clamping anchor (PopLok), and a spooling anchor (ReelX STT). Four constructs were compared for each type of anchor, with the anchor double or quadruple loaded with tape-type sutures or conventional sutures. The testing protocol comprised preloading suture tension to 10 N; cyclic loading, in which tension increased in increments of 10 N from 10 to 90 N; and a load-to-failure stage set at a speed of 0.5 mm/s. The clinical failure load (CFL) was defined as suture slippage of ≥3 mm. Also, 1-way analysis of variance and power analysis were used to compare the CFLs of the constructs. Results: For the quadruple-loaded spiral core clamping anchors, a significant reduction in CFLs was seen with conventional sutures over tape-type sutures (138.10 ± 4.73 vs 80.00 ± 12.25 N, respectively; P < .001). This reduction was not observed under the double-loaded condition (conventional vs tape type: 76.00 ± 5.48 vs 80.00 ± 10.00 N, respectively). Substitution of the suture materials did not significantly reduce the CFLs for the winged clamping anchors (conventional vs tape type: 40.00 ± 10.00 vs 30.00 ± 7.07 N for double loaded, respectively, and 64.00 ± 13.41 vs 50.00 ± 10.00 N for quadruple loaded, respectively) or the spooling anchors (conventional vs tape type: 62.00 ± 19.23 vs 56.32 ± 20.20N for double loaded, respectively, and 72.00 ± 21.68 vs 84.00 ± 13.42 N for quadruple loaded, respectively). Conclusion: Substituting tape-type sutures for conventional sutures increased the CFLs of some internal knotless anchors. With specific suture-anchor combinations, quadruple-loaded conventional suture anchors had CFLs higher than those of double-loaded conventional suture anchors. Clinical Relevance: When multiple tape-type sutures are used in conjunction with a clamping anchor, clinicians should note a possible reduction in CFLs and resultant early suture slippage.